Restorative Justice as a Resolution for the Crime of Rape with Child Perpetrators - Nur (2021)
A child who commits a criminal act can be called a child in conflict with the law. One of the crimes committed by children was rape, which involved elementary and junior high school children in Probolinggo; they reportedly raped a high school student until they became pregnant. Sexual crimes against children occur in Southeast Asian countries, such as the Philippines, Thailand, Sri Lanka, Malaysia, and Indonesia. The purpose of this study was to review restorative justice as an effort to resolve the criminal act of rape with child perpetrators. The research method used is normative juridical research, with the approach of laws and concepts and collecting primary legal material in the form of existing cases. This study found that the restorative justice process in juvenile crime is essential because there are essential things to focus on the regulation that requires the active role of the community, perpetrators, and victims of crime, including the affected community, in the restorative justice process. A fundamental balancing approach must also be taken, namely, first, imposing sanctions based on responsibility for recovering victims' losses as a consequence of criminal acts; second, rehabilitation and reintegration of actors; and third, strengthening community safety and security systems